50 years of studies on rodent populations in the Institute of Ecology, PAS - Bujalska, Gabriela; Grüm, Leszek; Walkowa, Wiera (Studia Ecologiae et Bioethicae, 2004)
A review of rodent studies conducted in the Institute of Ecology is presented. The investigations took place both in the laboratory (mostly on Mus muscidus) and field conditions (first of all on Apodemus flavicollis, Clethrionomys glareolus and Microtus arvalis). The aim of the studies varied in time, and was always preceded by detailed, and often new, considerations on methods to be applied. Theoretical assumptions also evolved with time: from simple density-dependent approach to population demography, through the idea of the importance of population structures, to individualistic approach and neighborhood systems. A substantial part of the studies was aimed at interrelations between rodent species in heterogeneous habitats. The International Biological Program resulted in papers devoted to interrelations between rodent (secondary) productivity and basic habitat features (like food resources and their spatial distribution). Special attention was paid to confined populations, and among the long term (37 years) studies on a bank vole population inhabiting Crabapple Island.